Identification of the natural origin of waterproofing pine pitch in historical Southwest Native American basketry through gas chromatography-mass spectrometry. (April 2020) - Maitland, Brian A.; Tune, Jesse W.; Grubb, Michael P.
Highlights: The natural origin of pine resin can be reliably identified using GC–MS techniques. This method can still be used to identify resin that has been heat-treated or aged. We identify pinyon pine exudate as the primary resin used to waterproof 14 historical Southwest Native American baskets. Abstract: Archaeological and ethnographic records document a long and rich history of plant-based resource use by Indigenous peoples of the American Southwest. The history of this resource use tells a complex story of human-environment relationships in this arid landscape. Indigenous peoples of the American Southwest have historically made use of pine pitch to waterproof their basketry. Here, we have identified the pine species origin of the pitch used to construct historical baskets utilizing gas chromatography-mass spectrometry. Resin samples were collected from the three main resinous plants in the Four Corners area: Pinus edilus, Pinus ponderosa, and Juniperus scoplulorum, and their GC chromatograms were analyzed for characteristic molecular components. Furthermore, some of these resin samples were heated to simulate the pitch-application process to ensure the characteristic molecular components were still present after baking. We have found that the ratio of γ-muurolene to longifolene provides a reliable indication of the pines species origin of the pitch, even after being exposed to elevated temperatures, and that all 14 of the historical baskets analyzed were waterproofed primarily with resinous material collected from the Pinus edilus species.